Gastrointestinal dysmotility and pancreatic insufficiency in 2 siblings with Donohue syndrome. Issue 8 (22nd December 2016) - Kostopoulou, Eirini; Shah, Pratik; Ahmad, Noman; Semple, Robert; Hussain, Khalid
Abstract : Donohue syndrome is a rare congenital syndrome of insulin‐resistance and abnormal glucose homeostasis, caused by mutations in the insulin receptor (INSR) gene. It is characterized by specific phenotypic and clinical features and the diagnosis is based on clinical, biochemical and genetic criteria. We report 2 siblings with Donohue syndrome (cases 1, 2) with multiple clinical and biochemical characteristics. Both patients shared the same mutation and presented with intra‐uterine growth restriction, failure to thrive, fasting hyperinsulinaemic hypoglycaemia and episodic post‐prandial hyperglycaemia. Less common clinical features were also present, such as atrial septal defect and biventricular hypertrophy, clotting disorders, abnormal liver function tests and nephrocalcinosis. Interestingly, 2 previously unrecognized manifestations of the syndrome were also identified: severe gastrointestinal dysmotility (case 1) and exocrine pancreatic insufficiency (case 2). The co‐existence of all the above clinical features makes these cases extremely rare. Gastrointestinal dysmotility should always be considered as a potentially fatal feature in patients with the syndrome, due to the complexity of the possible co‐morbidities. In addition, our clinical experience for the first time suggests that pancreatic exocrine insufficiency may offer a possible explanation for the growth retardation observed in some patients with this syndrome. Our finding that replacement treatment with pancreatic enzymes improved weight gain (case 2) implies that all patients with Donohue syndrome should be investigated for exocrine pancreatic insufficiency.